2019
DOI: 10.3389/fevo.2019.00229
|View full text |Cite
|
Sign up to set email alerts
|

Higher Frequency of Extra-Pair Offspring in Urban Than Forest Broods of Great Tits (Parus major)

Abstract: Urbanization increasingly changes the ecological conditions for wild animal populations, influencing their demography, reproduction, and behavior. While studies on the ecological consequences of urbanization frequently document a reduced number and poorer body condition of offspring in urban than in non-urban bird populations, consequences for other components of reproduction are rarely investigated. Mating with partners outside the social pair-bond is widespread in birds, and although theory predicts that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…For example, Lessels et al (1996) reported that the proportion of male offspring increased with hatching asynchrony in great tits. Furthermore, Pipoly et al (2019) found in the same populations and breeding seasons as in the present study that the number of extra-pair offspring was higher in urban habitats than in forests, which might influence sex ratio adjustment. The other possible interpretation of our findings is that the observed variance in brood sex ratios is largely random, with no facultative sex ratio adjustment going on (Ewen et al 2004).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, Lessels et al (1996) reported that the proportion of male offspring increased with hatching asynchrony in great tits. Furthermore, Pipoly et al (2019) found in the same populations and breeding seasons as in the present study that the number of extra-pair offspring was higher in urban habitats than in forests, which might influence sex ratio adjustment. The other possible interpretation of our findings is that the observed variance in brood sex ratios is largely random, with no facultative sex ratio adjustment going on (Ewen et al 2004).…”
Section: Discussionsupporting
confidence: 76%
“…To statistically compare the sex ratios between the two habitat types (urban sites vs. forest sites) we calculated linear contrasts from the full and reduced models. These linear contrasts were pre-planned comparisons between the two urban sites vs. the two forest sites (see also Pipoly et al 2019 and Vincze et al 2019 for the same approach to compare habitat types by pre-planned linear contrasts and for additional details of the method). Each linear contrast was back-transformed from the log-scale to provide the odds ratio (OR, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lessells et al [40] reported that the proportion of male offspring increased with hatching asynchrony in great tits. Furthermore, Pipoly et al [48] found in the same populations and breeding seasons as in the present study that the number of extra-pair offspring was higher in urban habitats than in forests, which might influence sex ratio adjustment. The other possible interpretation of our findings is that the observed variance in brood sex ratios is largely random, with no facultative sex ratio adjustment going on.…”
Section: Discussionsupporting
confidence: 70%
“…To statistically compare the sex ratios between the two habitat types (urban sites vs. forest sites) we calculated linear contrasts from the full and reduced models. These linear contrasts were pre-planned comparisons between the two urban sites vs. the two forest sites (see also Pipoly et al [48] and Vincze et al [68] for the same approach to compare habitat types by pre-planned linear contrasts and for additional details of the method). Each linear contrast was back-transformed from the log-scale to provide the odds ratio (OR, i.e.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In the second step, we used these linear models for each response variable to conduct the pre‐planned comparisons by calculating linear contrasts from each model's marginal means (package ‘emmeans') between the two forest and two urban sites (for similar approach see also Pipoly et al 2019, Vincze et al 2019) separately for FY and AFY birds. We compared habitats separately for the two age groups because they likely differed in their moulting conditions.…”
Section: Methodsmentioning
confidence: 99%